The External Conflicts Faced By Simon In Love, Simon Movie Script - Kadek Putri Pradnyaningsih; I Nengah Sudipa; Anak Agung Sagung Shanti Sari Dewi (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
The title of this paper is The External Conflicts Faced by Simon in Love, Simon Movie Script. This study is aimed at analyzing external conflicts faced by Simon as the main character. The data of this study were taken from Love, Simon movie script. In collecting the data of this study, the documentation method and note-taking technique were applied. The data were analyzed by applying descriptive qualitative method. Then in presenting the result of the data analysis, the informal method was applied. Theory of conflict (Kenney, 1966, p. 19) were used to analyze the data. The result of this study shows that the external conflicts faced by Simon occurred between man vs. man and man vs. society. Simon had external conflicts with other characters included Martin, Abby, Nick, Nora, Leah and Blue. Furthermore, the external conflict between Simon and the society happened between Simon and students at school.